The role of intestinal microbiota in the development of dysfunction of the biliary system in children - O. V. Kovaleva; L. A. Lityaeva; O. G. Zhilenkova (LLC "Diagnostics and Vaccines", 2024)
Objective: to study the state of the intestinal and biliary microbiota in children with intestinal and gallbladder dysfunction and to determine the features of the component composition of the biliary microbiota. Methods: We examined 20 children with irritable bowel syndrome (IBS). The presence of small intestinal bacterial overgrowth (SIBO) syndrome was determined (using a hydrogen breath test with lactulose), microbial markers of the intestinal and biliary microbiota (using gas chromatography-mass spectrometry). We also performed microscopy of bile (phase-contrast light microscopy) obtained through duodenal intubation. Results: In all children with IBS, SIBO was verified in the small intestine, with insufficiency of the ileocecal valve in half of them, associated with hypomotor dyskinesia of the gallbladder. Microscopy of the bile revealed a large number of crystals and leukocytes. A study of microbial markers of intestinal and biliary microbiota in all children with IBS and SIBO revealed excessive bacterial associative growth of gram-negative opportunistic bacteria in combination with viruses of the Herpes family. An increase in the level of lipopolysaccharides (2 times higher than normal) and a deficiency of microbial markers of the main groups of microorganisms (anaerobic bacteria) responsible for metabolization processes in the enterohepatic circulation (plasmalogen less than 50 μg/ml) were recorded. Excessive growth of 28 species of opportunistic bacteria was detected in bile in diagnostically significant concentrations associated with hypomotor dysfunction of the gallbladder and lithogenicity of bile. Conclusion: A violation of the biliary microbiota was established with an increase in the proportion of gram-negative opportunistic bacteria, the spectrum of which was close to that of the intestine and their association with intestinal and biliary dyskinesia